Chăm sóc bệnh nhân ung thư vú được phẫu thuật và xạ trị trong mổ tại bệnh viện Trung Uống Huế - Xuân, Phan Thị Kim; Hoa, Châu Thị; Hoài, Lê Thị; Thảo, Huỳnh Thị Minh; Dũng, Nguyễn Việt (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
A